Design of Green Marketing Strategy on XYZ Products with a SWOT Approach - Agra Gautama; Denpharanto Agung Krisprimandoyo; Fahrul Riza (Green Publisher Indonesia, 2025)
The construction sector, as one of the largest contributors to global greenhouse gas emissions, faces major challenges in achieving sustainability. XYZ, a company known for industrial product innovation, is committed to developing an effective Design of Green Marketing Strategy on XYZ Products with a SWOT Approach to strengthen its environmentally friendly image. This study aims to examine how the marketing mix can be utilized while addressing competition and price wars in the industry. It also explores the role of sales, marketing, and customer service teams in communicating the company’s sustainability commitments to B2B consumers. Using a qualitative approach and strategic planning technique, this study seeks to understand how XYZ’s Design of Green Marketing Strategy on XYZ Products with a SWOT Approach is created and applied in a competitive B2B context. Data collection includes in-depth interviews with internal teams and analysis of relevant company marketing documents. The SWOT framework is used to evaluate the strategy’s strengths, weaknesses, opportunities, and threats. The findings are expected to offer practical insights into developing a green marketing strategy that effectively integrates People and Product. Additionally, this research provides recommendations for enhancing XYZ’s eco-friendly image and countering greenwashing practices. By addressing the integration of the marketing mix in industrial product contexts, this study contributes to the evolving body of green marketing literature.